A Depiction of Poverty in Fiersa Besari’s Novel Tapak Jejak Using Ian Watt’s Sociological Approach - Syafitri, Eka Ari; Rahariyoso, Dwi; Afria, Rengki (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2023)
This study aims to describe the author’s social context in Fiersa Besari’s novel *Tapak Jejak*. It also aims to describe literature as a reflection of society in Fiersa Besari’s novel *Tapak Jejak*, as well as to describe the social function of literature in Fiersa Besari’s novel *Tapak Jejak*. This study was conducted by identifying, describing, and analyzing the author’s social context, literature as a mirror of society, and the social function of literature in the novel *MA YAN*, based on Ian Wat’s sociological approach to literature. This novel depicts the poverty experienced by the character Fiersa Besari and the people of Eastern Indonesia. The research method used in this study is qualitative descriptive. The data in this study consist of excerpts depicting poverty from the novel Tapak Jejak by Fiersa Besari. The data collection methods used in this study were reading and note-taking. Abstrak Penelitian ini bertujuan untuk mendeskripsikan konteks sosial pengarang dalam novel Tapak jejak karya Fiersa Besari. Mendeskripsikan sastra sebagai cerminan masyarakat dalam Novel Tapak Jejak Karya Fiersa Besari. Serta mendesripsikan fungsi sosial sastra dalam novel Tapak Jejak karya Fiersa Besari. Penelitian ini dilakukan dengan mengidentifikasi, mendeskripsikan, dan menganalisis konteks sosial pengarang, sastra sebagai cermin masyarakat dan fungsi social sastra dalam Novel MA YAN berdasarkan pendekatan sosiologi sastra Ian Wat. Novel ini menunjukkan gambaran kemiskinan yang terjadi pada sang tokoh Fiersa Besari dan Masyarakat Indonesia timur. Metode dalam penelitian ini adalah deskriptif kualitatif. Data dalam penelitian ini adalah kutipan-kutipan yang menggambarkan kemiskinan yang terdapat dalam Novel Tapak Jejak karya Fiersa Besari Teknik pengumpulan data dalam penelitian adalah teknik baca, dan teknik pencatatan.